Tree cover assessment and terrestrial arthropod composition of the Philippine tarsier (Tarsius Carlito] syrichta) habitat in Balugo Falls, Brgy. Salvacion, Tacloban City - Colasito, Shaira Elaine M. (2019)
There are three extant species of tarsiers in the world: Tarsius for those found in Sulawesi, Cephalopachus in Sundaland, and Carlito in Greater Mindanao. Tarsius syrichta is the species of tarsier found in the Greater Mindanao faunal region comprised of Leyte, Samar, Maripipi, Biliran, Dinagat, Siargao, Bohol, and Mindanao. A primary assessment of Philippine tarsier (Tarsius syrichta) habitat and resource availability in Balugo Watershed, Brgy. Salvacion, Tacloban City, Leyte, through tree cover assessment and arthropod survey is the focus of the study. The tree cover was calculated using the basal area and a species richness assessment of captured and observed arthropods. The density of the arthropods and species of trees are disregarded in the paper.
Eleven distinct orders were identified from the arthropods captured in Balugo Watershed with order Coleptera having the most number of families identified. This is followed by arthropods from order Lepidoptera and Orthoptera with three families each. The basal area of the study site was found to be 44215.17 centimeter square/ meter square for an area of study measuring 700 meter square. The tree cover for the surveyed area measures 63.16 meter square hectares raised to negative one. There is a substantial amount of saplings which provides substrates onto which tarsiers can cling on and allow movement across the area. The presence of big trees and dense bamboo thickets present offers possible sleeping sites.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.